Reflectionson the useofdelphitechniqueinresearchin nursing - Ariane Fazzolo Scarparo; Ana Maria Laus; Ana Lídia de Castro Sajioro Azevedo; Mara Rúbia Ignácio de Freitas; Carmen Silva Gabriel; Lucieli Dias Pedreschi Chaves (Rev Rene)
The aim of thispaper was to discussand think theoretically overthe use of the Delphitechniqueinnursing research. A study was performedfrom thereflective proposalof Dalkey. The techniqueallowsthe trialinformation, in order to reachconsensus of opinionabout a subject,allowsnursing professionalswithdiverse experiencesandexpertiseon certain issues, collaboration building a consensusof views, encouraging discussion ofissues which arerelevant tothe future ofnursing.Thedetailed study of thetechnique allowsaccurate understandingabout the positive aspectsof their use, being considered an innovativemethodological alternative. It is evidentthat thetechnique hasthe potential to supportresearchthat focus onthecontemporary scene,marked bynew formsof action,incorporatingideas andforecasting trendsthat characterizethe current practice ofnursing.